2021
DOI: 10.3389/ffgc.2021.768085
|View full text |Cite
|
Sign up to set email alerts
|

Continuous Parameterization of Leaf Area Index and Phenological Phases Within Deciduous Forests Based on Temperature Measurements

Abstract: The Leaf-Area-Index (LAI) is commonly used to characterize the plant canopy and is a fundamental indication of plant vitality and photosynthetic activity. The forest health status is not only vital for economical reasons, but also has a significant impact on global carbon sequestration. The LAI has a highly dynamic character among deciduous forests and is prone to significant seasonal fluctuations. Accurate continuous LAI measurements do provide valuable information on growth characteristics, but they require … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…Remotely sensed LAI measurements have been widely used to observe the intensity and extent of defoliation in deciduous and mixed forests (De Beurs and Townsend 2008 ). LAI measurements also provide direct quantification of leaf properties, photosynthetic activity, C uptake (Jarlan et al 2008 ; Boussetta et al 2013 ; Alton 2016 ; Brown et al 2020 ) and often used to estimate vegetation biomass utilizing remote sensing-based models (Zolles et al 2021 ). Our study results showed that the mean LAI values for deciduous forests decreased by about 25% in 2021 as compared to the pre-infestation LAI values in 2020, and by about 22% as compared to the post-infestation LAI values in 2022.…”
Section: Discussionmentioning
confidence: 99%
“…Remotely sensed LAI measurements have been widely used to observe the intensity and extent of defoliation in deciduous and mixed forests (De Beurs and Townsend 2008 ). LAI measurements also provide direct quantification of leaf properties, photosynthetic activity, C uptake (Jarlan et al 2008 ; Boussetta et al 2013 ; Alton 2016 ; Brown et al 2020 ) and often used to estimate vegetation biomass utilizing remote sensing-based models (Zolles et al 2021 ). Our study results showed that the mean LAI values for deciduous forests decreased by about 25% in 2021 as compared to the pre-infestation LAI values in 2020, and by about 22% as compared to the post-infestation LAI values in 2022.…”
Section: Discussionmentioning
confidence: 99%